The Role of Brand Trust and Brand Love in Mediating the Relationship between Brand Experience, Brand Associations, Brand Quality, and Consumer Loyalty in Online Shopping - Stalin David; Shakir Ali (PT. Mawadaku Sukses Solusindo, 2025)
This study investigates the impact of brand experience, brand associations, and brand quality on loyalty intention and repurchase intention among online consumers, with brand trust and brand love serving as mediating variables. A survey was administered to undergraduate and graduate students enrolled at five public universities in Northern India. The findings reveal that while brand experience, brand associations, and brand quality do not significantly influence loyalty intention, they exert a positive effect on repurchase intention. Furthermore, the results demonstrate that brand satisfaction influences affective commitment, whereas brand trust affects both affective and continuance commitment. Affective commitment is found to positively influence repurchase intention and loyalty, while continuance commitment does not exhibit a significant effect on these outcomes.